Community-based tourism in Thailand: The need and justification for an operational definition - Ramesh Boonratana (2018)
In Thailand, any form of tourism that is associated with local and/or indigenous communities is treated as community-based tourism, regardless whether they have actively participated in its development and management and/or if the communities have collectively benefitted from it. Furthermore, community-based tourism is often referred to by several terms, which are used with neither distinction nor agreement. Its definitions or variations of its definitions mostly describe the phenomenon, the objectives, or its principles. This manuscript looks at the characteristics of community-based tourism as it pertains to Thailand, and proposes the adoption of an operational terminology relevant to the practices observed without compromising its principles. Given that community-based tourism and associated terms in Thailand are viewed as complex and confusing, an operational definition will allow a better characterization of community-based tourism, assist in achieving its objectives, and possibly work towards its accreditation. Moreover, an operational definition will allow consumers, partners, investors, and other interested parties to distinguish it from similar forms of tourism.